TRANSFORMATION OF ISLAMIC EDUCATION BASED ON THE QUR'AN AN EXAMINATION OF THE PHILOSOPHICAL MEANING OF IQRA IN SURAH AL-'ALAQ - khoiruddin (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
Islamic Education has its primary foundation in revelation, with the Qur'an as the source of values that build the whole generation both intellectually, emotionally, spiritually, and morally. Surah Al-'Alaq verses 1-5 become the starting point for the transformation of Islamic Education through the command of "Iqra'" which demands multidimensional reading: texts, natural phenomena, and the self with a holistic approach. The reality of contemporary Education tends to emphasize the cognitive aspects and hard skills, but often ignores the strengthening of character, moral values, and spirituality, resulting in the emergence of dualism and identity crises. This research uses a philosophical maudhui (thematic) interpretation approach, namely collecting relevant verses, conducting philosophical analysis with philosophical logic and theory, and integrating revelation and ratio in interpreting the meaning of "Iqra'". The results of the study reveal that Surah Al-'Alaq encompasses educational values that encompass sensory, intellectual, emotional, spiritual, and supraconscious dimensions, all of which form the foundation of human development. The transformation of learning based on the values of revelation is crucial for building a civilized society and addressing current and future humanitarian crises, so that Islamic Education is not only oriented towards knowledge but also towards the development of character and spirituality as a whole.